Community mental health teams : a guide to current practices - Burns, Tom, 1946- (Oxford medical publications., 2004)
Community Mental Health Teams (CMHTs) have evolved over the last 30-40 years to serve patients with mental illnesses who would previously have been treated in large mental hospitals. This is the first book to provide practical advice for those working within these teams. It addresses the needs of the individual specialists within the CMHT, and provides clinical advice based on what has been seen to work. Written by a leading authority in this field, the book willbecome the standard text for all those specialists working within and close to community mental health teams.